2020
DOI: 10.1111/pirs.12557
|View full text |Cite
|
Sign up to set email alerts
|

Travel costs, trade, and market segmentation: Evidence from China's high‐speed railway

Abstract: Using high-speed railway construction as a natural experiment, this paper contributes to our understanding of how passenger-oriented transportation infrastructure affects interregional trade. The findings show that trade value increases and market segmentation decreases with high-speed railway (HSR) expansion, indicating that movement of people fosters movement of freight. The heterogeneous analyses suggest that technology-intensive industries and provinces with poorer pre-existing ICT level are impacted more.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 58 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…At the same time, industries with higher technology dependence and provinces with poorer preexisting ICT levels tend to benefit more from it. They also revealed the significant impact of HSR on information flow and knowledge spillover and that HSR could generate more room for freight services than another mode of transportation [7]. Additionally, Ma et al found out that HSR leads to an increase in entrepreneurship by 3.5%.…”
Section: Literature Reviewmentioning
confidence: 98%
“…At the same time, industries with higher technology dependence and provinces with poorer preexisting ICT levels tend to benefit more from it. They also revealed the significant impact of HSR on information flow and knowledge spillover and that HSR could generate more room for freight services than another mode of transportation [7]. Additionally, Ma et al found out that HSR leads to an increase in entrepreneurship by 3.5%.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Knowledge intensity, human capital level and labor cost are all important factors affecting the agglomeration of producer services. The rapid transit network expansion of urban agglomeration is conducive to expand the scope of high-quality innovative talents district, enlarge the radius of innovation talent service, improve the labor supply and demand match, strengthen the talent links between the city [27] and enhance the competitiveness of cities along, provide more face-to-face communication opportunities and route of transmission of knowledge for the industry department, so as to promote the development of producer services cluster. The free flow of high-quality labor force in the urban agglomeration improves the frequency of talent interaction, promotes the flow and sharing of knowledge within the industry, and thus mutual learning and mutual imitation form knowledge spillover effect.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Hence, reverse causality is not a concern in this study. To resolve the potential endogeneity problem that HSR construction is common in cities with more capital flow, an instrumental variable is constructed for a city's likelihood to be connected in the HSR network using the variation in historical railway network (Zheng and Kahn 2013;Duranton et al, 2014;Niu et al, 2020).…”
Section: A U T H O R Accepted Manuscriptmentioning
confidence: 99%
“…To handle potential heteroskedasticity and serial correlation, standard errors are clustered at the city level. Table1summarizes the descriptive statistics for the variables in To address the omitted variable problem in fixed effects model, this study follows the study byNiu et al (2020) and constructs a panel-structured instrument using historical railway connection. Their approach assumes that the total number of newly constructed HSR lines and stations at the country-level HSR plan is exogenously determined by the central…”
mentioning
confidence: 99%